2019
DOI: 10.1093/eurpub/ckz186.232
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer burden in Tunisia: situation in 2017 and projections by 2030

Abstract: Introduction Despite advances in diagnostic and treatment of cancer, burden of this disease is increasing worldwide. Breast Cancer is one of the leading cancers and major causes of death among female worldwide. The aim of this study was to describe the breast cancer burden in Tunisia in terms of disability adjusted life years (DALY) in 2017 and to perform projections by 2030. Methods DALYs for cancer are the sum of years of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In particular, which methodology was to be followed, based on which data were to be available, and how the retrieved evidence was to be synthesised. It should also be noted that despite the relatively high burden of disease and considerable percentage of health expenditure devoted to breast cancer in Tunisia [ 14,15 ]; at the time the assessment was published, the WHO had launched a pilot procedure for prequalification of biotherapeutic products including trastuzumab [ 36 ] and the market entry of biosimilars was likely to change the distribution and/or pricing of trastuzumab in the country.…”
Section: Summary Of Trastuzumab Economic Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, which methodology was to be followed, based on which data were to be available, and how the retrieved evidence was to be synthesised. It should also be noted that despite the relatively high burden of disease and considerable percentage of health expenditure devoted to breast cancer in Tunisia [ 14,15 ]; at the time the assessment was published, the WHO had launched a pilot procedure for prequalification of biotherapeutic products including trastuzumab [ 36 ] and the market entry of biosimilars was likely to change the distribution and/or pricing of trastuzumab in the country.…”
Section: Summary Of Trastuzumab Economic Evidencementioning
confidence: 99%
“…In Tunisia, breast cancer is the primary cancer in women and represents the most common cause of cancer mortality [ 11,12 ]. The standardised incidence of breast cancer in Tunisian woman has nearly tripled since 1994, reaching 50.17/100,000 persons years in 2017 [ 13,14 ]; it is projected to grow even further in coming years to eventually match the incidence of HICs. HER-2 positive breast cancer patients represent between 15 to 25% of all cases [ 15 ].…”
Section: Case Study: Trastuzumab In Tunisiamentioning
confidence: 99%
“…After three days 32,2 4. The different waiting times of the surgical pathway of women with breast cancer:…”
Section: Breast Cancer Surgical Pathwaymentioning
confidence: 99%
“…African Journal of Urology *Correspondence: Asma.hadhri@gmail.com 1 Radiotherapy Unit, Salah Azaiez Institute of Cancer, Boulevard du 9 avril 1938 Bab Saâdoun, 1007 Tunis, Tunisia Full list of author information is available at the end of the article Computed tomography body scan showed extensive bone progression and increased bladder tumor size.…”
Section: Open Accessmentioning
confidence: 99%
“…In Tunisia as in the rest of the world, breast cancer is the most common cancer in women. A Tunisian study published in 2017 found that breast cancer incidence rate among women was estimated to 50.17/100000 persons years [1].…”
Section: Introductionmentioning
confidence: 99%